Protective capacity of ice hockey helmets at different levels of striking compliance - de Grau, S.; Post, A.; Meehan, A.; Champoux, L.; Hoshizaki, T. B.; Gilchrist, M. D. (Sports Engineering, 2020)
In elite ice hockey, concussions occur from a variety of impact sources with different compliances, such as player-to-player collisions, impacts on the ice, boards, and glass. The effectiveness of ice hockey helmets to manage an impact under varying compliance conditions is currently unknown. The objective of this research was to determine the effect of striker compliance on ice hockey helmet performance. Striking caps of different compliance were used to impact a helmeted and unhelmeted Hybrid III headform at three locations. The headform kinematics was measured in linear and rotational acceleration, rotational velocity. The linear and rotational time histories were then used as input to a finite element model of the human brain to determine maximum principal strain response. Helmeted conditions produced significantly lower linear and rotational acceleration, and rotational velocity for the three levels of compliance at the three impact locations. The reductions through the use of a helmet were higher at low compliance in comparison to the other compliance conditions. Considering player-to-player collisions are the most common source of concussion in adult ice hockey, and also the most compliant, these data support the development of helmet technologies that can mitigate impacts under higher compliance conditions to reduce the risk of brain trauma.